2020
DOI: 10.1038/s41598-020-77302-9
|View full text |Cite
|
Sign up to set email alerts
|

ROCK inhibitors beneficially alter the spatial configuration of TGFβ2-treated 3D organoids from a human trabecular meshwork (HTM)

Abstract: To elucidate molecular pharmacology of Rho-associated coiled-coil containing protein kinase inhibitors (ROCK-i, Ripasudil and Y27632) on their efficiency for aqueous outflow, 2D or 3D cultures of a human trabecular meshwork (HTM) were prepared in the presence of TGFβ2. Those were examined by transendothelial electrical resistance (TEER, 2D), electronic microscopy (EM, 2D and 3D), expression of the extracellular matrix (ECM) including collagen1 (COL1), COL4 and COL6, and fibronectin (FN) by immunolabeling and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
107
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(121 citation statements)
references
References 45 publications
12
107
2
Order By: Relevance
“…ROCK-is on their TGF-β2-induced fibrogenetic changes [38]. Therefore, in the present study, to elucidate the effects of the stimulation of PPARγ by Rosi or the inhibition of ROCKs by pan-ROCK-i, ripasudil hydrochloride hydrate (Rip) or ROCK2-i, KD025 on TGF-β2-induced fibrogenetic changes of human conjunctival fibroblasts (HconF), 2D and 3D cultured HconF cells were used.…”
Section: Effects Of the Stimulation Of Pparγ Or The Inhibition Of Rocks On Tgf-β2-treated 2d Hconf Monolayersmentioning
confidence: 99%
See 1 more Smart Citation
“…ROCK-is on their TGF-β2-induced fibrogenetic changes [38]. Therefore, in the present study, to elucidate the effects of the stimulation of PPARγ by Rosi or the inhibition of ROCKs by pan-ROCK-i, ripasudil hydrochloride hydrate (Rip) or ROCK2-i, KD025 on TGF-β2-induced fibrogenetic changes of human conjunctival fibroblasts (HconF), 2D and 3D cultured HconF cells were used.…”
Section: Effects Of the Stimulation Of Pparγ Or The Inhibition Of Rocks On Tgf-β2-treated 2d Hconf Monolayersmentioning
confidence: 99%
“…The 3D HconF sphenoids were prepared following a recently published method for 3D cultures of human orbital fibroblasts (HOFs) [37,42] or human trabecular meshwork cells (HTM) [38]. Briefly, HconF cells at 90 % confluence as above were washed with phosphate buffered saline (PBS), detached using 0.25 % Trypsin/EDTA, and re-suspended in 3D medium composed of 2D medium supplemented with 0.25 % methylcellulose (Methocel A4M) after centrifugation for 5 min at 3000× g. Approximately 20,000 HconF cells in 28 µL of 3D medium were cultured in each well of the hanging drop culture plate (# HDP1385, Sigma-Aldrich, St Louis, MO, USA) (day 0).…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…Briefly, at approximately 80% confluence, 5 ng/mL TGFβ2 and ROCK-i, 10 μM Rip or KD025 were added the apical side of the wells (Day 1), and cultured until Day 6. At Day 6, the wells were washed twice with PBS, and TEER (Ωcm 2 ) were measured using an electrode (KANTO CHEMICAL CO. INC., Tokyo, Japan) 20 .…”
Section: Methodsmentioning
confidence: 99%
“…In fact, several studies revealed that ROCK inhibitors (ROCK-is) have hypotensive effects toward intraocular pressure (IOP) in several animal models 15 , 16 , and one of the ROCK-is, ripasudil hydrochloride hydrate (Rip), a non-selective ROCK-i, is already available as an anti-glaucoma medications for the treatment of glaucoma and ocular hypertension 17 , 18 . We recently developed three-dimension (3D) drop cell cultures using human TM (HTM) in conjunction of TGFβ2, which was revealed to increase transcellular pressure and suppress ease of outflow 19 , to replicate a relevant ex vivo glaucoma TM model 20 . Using this model, we found that TGFβ2 induced significantly smaller and stiffer 3D HTM sphenoids, and such TGFβ2 induced effects were substantially reduced by the presence of the pan ROCK inhibitors, Rip or Y27632 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation